Evaluasi program anti-bullying berbasis digital literacy untuk mencegah cyberbullying di kalangan remaja - Rahmawati, Kurnia (Maliki Interdisciplinary Journal, 2026)
In this article, we will discuss bullying, which is a type of violence that is a big problem in the educational environment, especially among high school/vocational high school teenagers. Bullying has an impact on the social development and mental health of the victim. Online bullying, or cyberbullying, has emerged along with technological advancements. This happens through digital media and is difficult to monitor because it can reach victims anytime and anywhere. Programs that focus on digital literacy are considered an effective solution to prevent cyberbullying targeting adolescents. The purpose of this program is to evaluate how effective digital literacy-based educational interventions are. This activity uses a participatory approach, with interactive lectures, group discussions, case simulations, and training to create positive digital content. The results of the evaluation showed that students had a better understanding of bullying and digital literacy materials. Participants can understand the different types of harassment, know its psychological effects, and raise awareness of digital ethics, such as the principle of "think before posting" and the importance of safeguarding personal data. In addition, they are aware that actions taken in cyberspace have a real impact on social and legal life. This contextual and empathetic educational method has proven to be effective in fostering intelligent attitudes when using digital media. So, digital literacy-based programs really help teens learn about the dangers of cyberbullying. Digital responsibility has been well instilled through these interventions, which are critical to building a safe, inclusive, and violence-free digital environment.